Solving an improved heat transmission measuring equation using partial differential equations with variable coefficients - Sabah Abbas, Elaf; Kuffi, Emad; Faleh Maktoof Al Khozai, Sarah (International Journal of Engineering and Technology, 2019)
An application, for all of its importance in engineering or not, has a need to be less complex while covering a wide range of variables. In this paper, the Al-Tememe transformation was used to solve the linear partial differential equations with variable coefficients, and applied on an improved heat transmission measuring equation. It was found that the range of the heat transmission measuring equation variables had increased, including the time and temperature observation point variables.Â